Pengaruh Bimbingan Kelompok Dengan Metode Muhadharah untuk Meningkatkan Keterampilan Public Speaking Mahasiswa - Ariwibowo; Manah Rasmanah; Bela Janare Putra (Social Science and Contemporary Issues Journal, 2024)
This research is entitled "The Influence of Group Guidance with the Muhadharah Method to Improve Students' Public Speaking Skills" Public speaking skills are very important skills in the academic and professional world. Students as future leaders need to master these skills to be able to communicate ideas, opinions, and ideas clearly and effectively to their audience. The purpose of this study is to find out how students' public speaking skills before and after and whether they have an effect after being given group guidance using the muhadhrah method. This research method uses a quantitative approach with the type of experimental research and the design of one group pretest - posttest. From the total population of 84 students, 8 samples were taken. The sample technique used is purposive sampling. Data collection techniques include observation, questionnaires, and documentation. With a total of 22 questions that have been tested for the validity of the calculation > the table with a calculation value of 0.052-0.510 and the table 0.217. The data analysis technique uses the Wilcoxon test. The results of the study showed that the majority of Himasada students' public speaking skills were in the high category, which was initially with a value of M(SD) = 32.5(2.72) to M(SD) = 51.125(1.246). Therefore, Group Guidance with Muhadharah Motto is effective in improving the Public speaking skills of students with a high influence category.